The testing of photoscan 3D object modelling software - Jiroušek, Tomáš; Kapica, Roman; Vrublová, Dana (Geodesy and Cartography, 2014)
The paper presents triangulation-based accuracy test procedures for PhotoScan 3D modelling software with automatic features including camera station identification, point cloud construction and the generation of polygon networks and polygon net textures. The process starts with establishing the camera resolutions. Then, internal orientation elements of the cameras are established by means of different calibration techniques and comparisons between them are made. 3D models are then tested using diverse model generation parameters and different configurations of sets of images including how each type of calibration affects the resulting 3D model accuracy. To conclude, 3D model accuracy is compared with geodesic surveying results.